2007
DOI: 10.1093/protein/gzm032
|View full text |Cite
|
Sign up to set email alerts
|

Influence of different carboxy-terminal mutations on the substrate-, reaction- and enantiospecificity of the arylacetonitrilase from Pseudomonas fluorescens EBC191

Abstract: Different members of the nitrilase superfamily (D-carbamoylases, Nit-Fhit proteins, amidases, cyanide dihydratases and nitrilases) were compared by multiple sequence alignments and a long carboxy-terminal extension (about 50 amino acids) identified in all nitrilases and cyanide dihydratases which was not present in other members of the nitrilase superfamily. The function of this C-terminal part was experimentally analysed in the arylacetonitrilase of Pseudomonas fluorescens EBC191 by the construction of variou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
52
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(59 citation statements)
references
References 2 publications
7
52
0
Order By: Relevance
“…Multiple-sequence alignments demonstrated that the corresponding tyrosine residue is highly conserved among different nitrilases and amidases from bacterial, plant, or fungal sources (21,45). The importance of this residue for the catalytic activity of nitrilases was experimentally verified during our studies, as several of the enzyme variants generated (e.g., Tyr54Ile, Tyr54Lys, and Tyr54Arg) were completely inactive for the conversion of acetophenone cyanohydrin, mandelonitrile, and 2-phenylpropionitrile.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…Multiple-sequence alignments demonstrated that the corresponding tyrosine residue is highly conserved among different nitrilases and amidases from bacterial, plant, or fungal sources (21,45). The importance of this residue for the catalytic activity of nitrilases was experimentally verified during our studies, as several of the enzyme variants generated (e.g., Tyr54Ile, Tyr54Lys, and Tyr54Arg) were completely inactive for the conversion of acetophenone cyanohydrin, mandelonitrile, and 2-phenylpropionitrile.…”
Section: Discussionsupporting
confidence: 54%
“…The construction of plasmids pIK7, pIK9, and pDHE22, which encode the nitrilases from Alcaligenes faecalis ATCC 8750, Pseudomonas fluorescens EBC191, and Synechocystis sp. strain PCC6803, respectively, was described previously (16,20,21). The gene for the rhodococcal nitrilase was amplified from a nitrileconverting Rhodococcus rhodochrous strain.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This enzyme forms with certain nitriles also significant amounts of the corresponding amides as side products (3,5,8,15,19,24). The enzyme has recently been studied intensively in order to analyze the molecular basis for the substrate specificity, reaction specificity, and enantiospecificity of nitrilases (9,10). In the course of these investigations, the effects of various carboxy-terminal mutations and mutations in close proximity to the catalytic active cysteine residue were analyzed.…”
mentioning
confidence: 99%
“…In the course of these investigations, the effects of various carboxy-terminal mutations and mutations in close proximity to the catalytic active cysteine residue were analyzed. These experiments demonstrated that deletions of 47 to 67 amino acids (aa) from the carboxy terminus of the nitrilase resulted in variant forms that demonstrated increased amide formation and an increased formation of the (R)-acids (9). In addition, it was demonstrated that the size of the amino acid residue in direct proximity to the catalytic active cysteine residue (toward the C terminus) is determinative of the enantioselectivity of acid formation.…”
mentioning
confidence: 99%